Intergovernmental coordination and fiscal performance - RIBEIRO, Leonardo Cezar; GASPARINI, Carlos Eduardo; CALDEIRA, Thiago Costa Monteiro (Journal of Economics and Political Economy, 2024)
Abstract. This article evaluates the intergovernmental coordination of fiscal policy in Brazil, measured in terms of the synchronisation of fiscal responses adopted by the central and state governments between 2004 and 2016. An econometric analysis of Brazilian states' responses to central government fiscal impulses is conducted, controlling for variables that can affect states' fiscal performance, such as output gap, solvency, Dependency on intergovernmental transfers, expenditure decentralisation, and budget rigidity. The results show signs of a pro-cyclical nature in Brazilian states' fiscal outcomes, whereby a 1% increase/decrease in the central government's fiscal impulse leads to a 0.13% increase/decrease in the states' fiscal impulse. Evidence also found that greater dependency on intergovernmental transfers impairs states' fiscal performance. On the other hand, decentralisation of spending, high indebtedness, and greater budget rigidity are factors that lead to better fiscal discipline. The importance of this study consists in highlighting intergovernmental coordination as a strategy to ensure better efficiency of fiscal policy in the stabilizing and allocative functions of the budget. Keywords. Fiscal federalism, Fiscal coordination, Decentralisation, Public finance. JEL. H77, H68, E60.